Recruitment of antigen-specific CD8+ T cells in response to infection is markedly efficient - Heijst, Jeroen W. J. van (2009)
The magnitude of antigen-specific CD8+ T cell responses is not fixed but correlates with the severity of infection. Although by definition T cell response size is the product of both the capacity to recruit naïve T cells (clonal selection) and their subsequent proliferation (clonal expansion), it remains undefined how these two factors regulate antigen-specific T cell responses. We determined the relative contribution of recruitment and expansion by labeling naïve T cells with unique genetic tags and transferring them into mice. Under disparate infection conditions with different pathogens and doses, recruitment of antigen-specific T cells was near constant and close to complete. Thus, naïve T cell recruitment is highly efficient, and the magnitude of antigen-specific CD8+ T cell responses is primarily controlled by clonal expansion.